Uji Penurunan Kadar Glukosa Darah Ekstrak Etanol 70% Daun Dewandaru (Eugenia Uniflora L.) Kombinasi dengan Metformin pada Tikus Jantan Wistar Diinduksi Na2EDTA - Gusti Ayu Rai Saputri; Gunawan Pamudji Widodo; Dwi Ningsih (Jurnal Farmasi Indonesia, 2011)
Diabetes mellitus is a disease that affects many people. Dewandaru (Eugenia uniflora L.) leavesis a traditional medicinal plant contains saponins, flavonoids, tannins which one of the benefits to treat diabetes mellitus. Aimedof this study to identify and seek the most effective combination dose of 70% ethanol extract dewandaru leaves in combined with metformin to decrease blood glucose levels in Wistar male rats. Dewandaru leaves macerated with 70% ethanol solvent, condensed macerate obtained was tested in each group of test animals. Thirty rats were divided into 6 groups. Group I was given 70% ethanol extract of dewandaru leaves 300 mg/200 gBW, the second group (negative control) was given Na2EDTA 14 mg/200 gBW, group III (positive control) was given metformin 4.5 mg/200 gBW, group IV, V and VI was given the extract doses of 75 mg / 200 gBW, 150 mg/200 gBW and 300 mg/200 gBW combine with metformin 4.5 mg/200 gBW repectively. The treatment conduct for 12 days, 3 days induced with Na2EDTA, and then for 9 days given treatment according to each group. The glucose levels were determinated day 0, the 3rd, 6th, 9th and 12th. Then the data obtained were analyzed by one way ANOVA with a level of 95%. The result showed a decrease in blood glucose levels significantly between the treatment group 70% ethanol extract of dewandaru leaves dose of 75 mg, 150 mg and 300 mg/200 gBW in combine with metformin. 70% ethanol extract of dewandaru leaves dose of 75 mg/200 gBW in combine with metformin iseffective dose that coulddecrease blood glucose levels with three days theraphy.